Analisis Eksistensi Badan Hukum Koperasi Sebagai Sarana Kemajuan Umkm Di Indonesia - Bonaraja Purba; Hasyim; Asshofi Fadhillah Harahap; Laura Elfina Karo Karo; Lily Syafitri Batubara; Sri Dai Sulfina (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
The purpose of this study is to see how the existence of cooperative legal entities as a means of advancing MSMEs in Indonesia and to see how MSME regulations in Indonesia are according to existing legal rules. The research method used in this research is descriptive in nature. Where this research utilizes literature studies. This activity is carried out by collecting information related to the subject or problem under study through books, journals, the internet and other sources of information. The results of the study show that merging MSMEs is seen as being able to better support the national economy because it is a family-based business in addition to carrying out the tasks and functions that have been set in the cooperative.